Modern Web development with IBM WebSphere - Brown, Kyle (IBM Press, 2014)
This guide presents a strategy for building modern mobile/web applications, offering practical, hands-on coverage of front-end development with IBM WebSphere Application Server 8.5, IBM Worklight, and the most popular open source frameworks. The authors introduce best practices for MobileFirst development to help create apps that work on mobile devices and add features on conventional browsers and present ways to deliver Web 2.0 apps with HTML/JavaScript front ends, RESTful Web Services, and persistent data. Coverage includes: developing for MobileFirst; delivering lightweight JEE apps with WebSphere Application Server's new Liberty Profile; implementing an agile, user-centered, page-oriented approach to design; constructing REST services with WebSphere Liberty, Eclipse, and JEE annotations; building better front-end application architectures with frameworks and JavaScript; designing and building complex, transactional RESTful services that interface with databases and other data sources; building IBM Worklight hybrid apps with open source frameworks: jQuery Mobile, Backbone, Require.js, and Handlebars; debugging cross-platform, multi-language modern web apps; and promoting scalability, security, and connectivity into the wider enterprise.
Includes bibliographical references and index. - Print version record
Keywords: WebSphere; Web site development; Sites Web; Développement